Kearifan Ekologi Masyarakat Bayung Gede dalam Pelestarian Hutan Setra Ari-Ari di Desa Bayung Gede, Kecamatan Kintamani, Kabupaten Bangli - Eka Putri, Dewa Ayu (Humanis, 2015)
During the 2000s, discourse on the environment increased because of the destruction of forests in many countries, including Indonesia and even Bali. This study aims to reveal the ecological wisdom that tends to be preserved by indegenous people in their efforts to conserve forests. Bayung Gede Village is one of the Bali Mula village that still maintains a nobel tradition that contains ecological wisdom for the conservation of its forest, which is called the forest of Setra Ari-Ari (placenta grave). This study raises two issues: the first isssue is about why Bayung Gede community conserves the Setra Ari-Ari forest and the second explores symbolic meaning of Setra Ari-Ari to the people of Bayung Gede. This research is a qualitative ethnographic study using an ethnoecology approach and the Geertz interpretative theory. Within these frameworks the study focuses on the idea of ecological wisdom, the Bali Mula concept in Bayung Gede, and the symbolic meanings associated with forests, specifically the Setra Ari-Ari forest. The study arrives at two conclusions. The first, reveals a hidden rationality in the relationship and mythology of the Bayung Gede community regarding the Setra Ari-Ari forest, especially in relation to the bukak tree. It exposes the benefits from the Setra Ari-Ari forest for the Bayung Gede community, both in terms of ritual needs and in terms of the environment as well as the Ulu Apad System, and awig-awig or village regulations that protect Setra Ari-Ari forest. The second expresses the symbolic meaning of Setra Ari-Ari for people of Bayung Gede which includes the tradition of hanging placentas in the forest, a paractice related to the  concept of Catur Sanak. It also explores hidden meaning of the Setra Ari-Ari region itself, bukak fruit and the placenta containers (made of split, brown coconut).
Keywords: Setra Ari-Ari, Bukak fruit, catur sanak